Endothelial Dysfunction in Atherosclerosis: Experimental Models and Therapeutics - Kopych, Vadym; Da Costa, Avelino Dos Santos; Park, Kwideok (The Korean Society for Biomaterials | BioMed Central, 2025)
Atherosclerosis is a cardiovascular disease that involves complex and multifactorial processes that are instigated from endothelial dysfunctions. In this review, we address endothelial dysfunction in atherosclerosis and the mechanisms, where they are characterized by structural and functional alterations in endothelial cells (ECs), as caused by inflammation, oxidative stress, or disturbed shear stress. In particular interest, we provide a comprehensive overview of the experimental models (in vitro and in vivo) used to investigate endothelial dysfunction, specifically the role of ECs in atherosclerosis. Finally, current therapeutics, for example, pharmacological interventions, cell and gene therapies, and nanomedicine, are introduced, along with emerging technologies for advanced treatment of atherosclerosis. This review will help readers better understand current scientific findings, experimental models, and technologies in an effort to decipher the mechanisms of atherosclerosis and to advance therapeutic interventions.